Breast Cancer Detection From Thermography Based on Deep Neural Networks - Kiymet, Seyfullah; Aslankaya, Muhammet Yavuz; Taskiran, Murat; Bolat, Bulent (IEEE, 2019)
Breast cancer is one of the most common types of cancer that affects more than 15% of women throughout their lives. Early detection of this type of cancer is crucial for the positive outcome of the treatment process. There are several screening methods for the detection of breast cancer. In this study, a new method based on thermal imaging is proposed for the detection of breast cancer. Four deep learning networks that were successful in object recognition competitions in recent years were used for breast cancer detection from thermographic breast images and as a result of experimental studies, ResNet50 network achieved the highest test performance in detection of breast cancer by 88.89%. This study demonstrated the applicability of deep learning networks in breast cancer detection.
Keywords: breast cancer detection; thermography; image processing; deep neural networks; logistic regression; Computer Science